Increased corrosion resistance of the AZ80 magnesium alloy by rapid solidification. Issue 8 (10th December 2014) - Aghion, E.; Jan, L.; Meshi, L.; Goldman, J.
Abstract Magnesium (Mg) and Mg‐alloys are being considered as implantable biometals. Despite their excellent biocompatibility and good mechanical properties, their rapid corrosion is a major impediment precluding their widespread acceptance as implantable biomaterials. Here, we investigate the potential for rapid solidification to increase the corrosion resistance of Mg alloys. To this end, the effect of rapid solidification on the environmental and stress corrosion behavior of the AZ80 Mg alloy vs. its conventionally cast counterpart was evaluated in simulated physiological electrolytes. The microstructural characteristics were examined by optical microscopy, SEM, TEM, and X‐ray diffraction analysis. The corrosion behavior was evaluated by immersion, salt spraying, and potentiodynamic polarization. Stress corrosion resistance was assessed by Slow Strain Rate Testing. The results indicate that the corrosion resistance of rapidly solidified ribbons is significantly improved relative to the conventional cast alloy due to the increased Al content dissolved in the α‐Mg matrix and the correspondingly reduced presence of the β‐phase (Mg17Al12). Unfortunately, extrusion consolidated solidified ribbons exhibited a substantial reduction in the environmental performance and stress corrosion resistance. This was mainly attributed to the detrimental effect of the extrusion process, which enriched the iron impurities and increased the internal stresses by imposing a higher dislocation density. In terms of immersion tests, the average corrosion rate of the rapidly solidified ribbons was <0.4 mm/year compared with ∼2 mm/year for the conventionally cast alloy and 26 mm/year for the rapidly solidified extruded ribbons. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1541–1548, 2015.